Negotiating Powerlessness : Everyday Forms of Resistance among Filipino Domestic Workers in Malaysia - Lumayag, Linda Alfarero (2004)
The international migration of labour is an important feature in the world economy today. Malaysia is a typical example of a country that heavily relies on foreign workers to fill in jobs in the services sector. With this, Malaysian homes also employ foreign domestic workers to carry out the social reproductive functions performed earlier by Malaysian women who now actively participate in the labour force. This is a study of power relations between actors of transmigration and the Filipino domestic workers in Malaysia. It looks at the issue of powerlessness of women workers in the domestic employment, and examines the daily forms of resistance against conditions of powerlessness. The central argument that runs through this study is that powerlessness is embedded in the socio-cultural structure of society which stifles their interests as women. This qualitative study involves 64 Filipino domestic workers who have been working in Malaysian households. Observations are drawn from a year-long immersion and interview with domestic workers, five employers and four employment agents and embassy staff as well as informal conversations with those who are involved in migrant issues. A triangulation of interview, observation and focus group discussion was used to gather information from the informants. Findings revealed that globalisation has intensified the movement of Filipino workers, especially women, across countries where domestic employment is available and made women more visible in the international division of social reproductive labour. Such visibility is viewed in terms of their physicality but is not translated in terms of their increasing empowerment as social actors in migration. Filipino women's propensity to migrate is gendered and is reflective of the subordinate position they are placed in Philippine society. This study also shows that women domestic workers are powerless right from the beginning of the migration process, when they start their domestic work in Malaysia, and until their eventual return in the home country. The condition of powerlessness is pervasive at the level of relations with employers and the society at large, made worse by the fact that they are foreign domestic workers. This condition of powerlessness also made them aware of the conscious resistance that has becomethe workers way of life thereby employing strategies and tactics to surmount whatever personal and employment-related problems. This study concludes that Filipino domestic workers are conscious of the different realms of powerlessness they experience through their own social network to the extent that daily forms of resistance are not developed on their own but shared collectively by the social network. Patterns of resistance are simply reactionary measures against exploitation and abuse and they do not feature transformative ways in order to subvert powerlessness; although, at the same time, these may empower them. More often, the daily forms of resistance tend to reinforce and strengthen their own powerlessness they actively participate. Legal protection for foreign domestic workers should be a concern of the Malaysian government in order to protect the interests of all related parties.